Middle East Christianity
XIII, 159 p.
Keywords: ‘The multitude of studies on religious groups in the Middle East neglected one of its basic components: Oriental Christians. The scholars in this book intelligently fill the gap by being united in a historical sociology framework. By analyzing 19th century missionaries and papal diplomacy they show globalization avant la lettre but also admirably update the dialectics of this group’s interaction within a region dominated by Islam’s cultural hegemony. More than the sum of its chapters.’ —Baghat Korany, Professor, Department of International Relations and Political Economy, American University Cairo, Egypt and Lead Author of the UNDP 10th Anniversary Arab Human Development ‘This insightful study provides a welcome addition to existing literature on Middle Eastern Christianity. By locating historical and contemporary Middle Eastern Christianity within the conceptual framework of world society, the volume goes beyond descriptive analyses of case study communities and countries. Instead, it contributes to our understanding of the complexities of globalization on Middle Eastern Christianity by exploring its impact at the macro, meso and micro levels.’ —Fiona McCallum Guiney, Senior Lecturer, School of International Relations, University of St. Andrews, United Kingdom Drawing from theories of world society and from historical-sociological theories the book studies the past, present, and future of Middle East Christianity. It focuses on the interplay between local practices and post-colonial entanglements in global modernity. The chapters of this book engage, inspired by these theories, key empirical dynamics that affect Middle East Christianity. This includes a historical overview on the history of Christians in the region, the relationship between Islam and Christianity, as well as case studies on the Maronites in Lebanon, Egypt’s Copts, the role of Protestant missionaries in the 19th century, processes of individualization amongst Middle East Christians, as well as papal diplomacy in the region. Stephan Stetter is Professor of International Politics and Conflict Studies at the Bundeswehr University Munich, Germany. Mitra Moussa Nabo is Research Associate at the National Centre for Crime Prevention in Bonn and Adjunct Lecturer at the Bundeswehr University Munich, Germany. .